2020
DOI: 10.1186/s13287-020-01937-8
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-derived extracellular vesicles alter disease outcomes via endorsement of macrophage polarization

Abstract: Mesenchymal stem cells (MSCs) are adult stromal cells that reside in virtually all postnatal tissues. Due to their regenerative and immunomodulatory capacities, MSCs have attracted growing attention during the past two decades. MSC-derived extracellular vesicles (MSC-EVs) are able to duplicate the effects of their parental cells by transferring functional proteins and genetic materials to recipient cells without cell-to-cell contact. MSC-EVs also target macrophages, which play an essential role in innate immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 113 publications
4
52
0
Order By: Relevance
“…From our systematic review, we found that MSCs induce M2 macrophages, consistent with findings in previous studies. With the increasing relevance of cell therapy, the anti-inflammatory and immunomodulatory nature of MSCs through M2 macrophages makes MSCs an attractive therapeutic option for many diseases [69]. MSC-mediated macrophage polarization has been shown to be beneficial in a myriad of conditions ranging from traumatic spinal cord injury to tendon rupture to dilated cardiomyopathy [70].…”
Section: Discussionmentioning
confidence: 99%
“…From our systematic review, we found that MSCs induce M2 macrophages, consistent with findings in previous studies. With the increasing relevance of cell therapy, the anti-inflammatory and immunomodulatory nature of MSCs through M2 macrophages makes MSCs an attractive therapeutic option for many diseases [69]. MSC-mediated macrophage polarization has been shown to be beneficial in a myriad of conditions ranging from traumatic spinal cord injury to tendon rupture to dilated cardiomyopathy [70].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of MSCs has been shown to induce M2 polarization through various pathways [ 106 , 151 , 152 , 153 , 154 , 155 , 156 , 157 ]. MSC exosomes contain miR-322, which suppresses the expression of pknox1, a protein that encourages the M1 phenotype, thus promoting M2 [ 157 ].…”
Section: Effect Of Msc Derived Extracellular Vesicles On Neuro-vascular Unit After Strokementioning
confidence: 99%
“…MSC-EVs have been reported to provide beneficial effect on neurons through various mechanisms. miR-210, which can be delivered via MSC-EVs, show various effects on neurogenesis following brain injury, possibly due to differences in time of administration [ 151 , 159 , 160 , 161 ]. Inflammatory factors IL-6 and TNF-α secreted by microglia after injury have been shown to decrease the survival of Doublecortin-positive (Dcx+) cells in vitro [ 159 ].…”
Section: Effect Of Msc Derived Extracellular Vesicles On Neuro-vascular Unit After Strokementioning
confidence: 99%
“…However, the parallel investigation of EVs secreted by MSCs of different origin emphasized the heterogeneity of their effects. For example, EV regulation can make prominent both the innate and adaptive immune reactions; the EVinduced altered effects can appear in several immune cells, not only various lymphocytes but also natural killer cells, dendritic cells and especially macrophages; MSC-EVs can govern immune-modulatory effectors or transmit active signal molecules, thus participating in various distinct processes such as differentiation, activation, proliferation and also suppression of immune cells [11][12][13][14]. Moreover, MSC-EVs from different tissues (bone marrow, adipose tissue, and umbilical cord) exhibit different cargo proteins [15].…”
Section: Innovative Role 0f Msc-evmentioning
confidence: 99%